The role of industrial design in modern manufacturing - Dautov E.N., Dautov E.N. (Рroblems of engineering and professional education, 2022)
This article is devoted to the importance of industrial design in production. The influence of design on the development of products and describes the main activities of the technical designer in today’s world. It tells about the development of ergodesign and the formation of styling in different countries.